Discrete dividends and the FTSE-100 index options valuation - Areal, Nelson (2014)
This paper studies the effect of discrete dividends on the FTSE-100 index options valuation, following closely Harvey and Whaley's [J. Fut. Mkts, 1992, 12(2), 123–137] study on the S&P-100 index. To the best of our knowledge, no such study has ever been performed on FTSE-100 options, where the dividends have a discreteness pattern different from the S&P-100. Unlike the Harvey and Whaley study, both American and European options are considered, a more accurate benchmark is proposed, and a comprehensive comparison of the accuracy of a larger set of valuation methods is performed. It is shown that there are significant differences in accuracy and speed among different methods, and that, for both American and European options, a great deal of accuracy can be gained by using an approximation that takes into account the discrete nature of the FTSE-100 index option dividends.